Intestinal injury signaling pathway in sepsis - Liu, Lin; Yue, Qin; Chen, Jinhao; Liu, Hui; Zeng, Xinyi (Frontiers in Immunology, 2025)
Sepsis is a syndrome of inflammatory response syndrome (SIRS) triggered when the host is exposed to bacterial, viruses, and other infectious agents. The resulting inflammation compromises intestinal integrity, and this gut injury subsequently amplifies systemic inflammation, ultimately leading to multiple organ failure. This review synthesizes recent advances in sepsis-induced intestinal injury, focusing on four key aspects: pathogenesis, molecular mechanisms, crosstalk among relevant signaling pathways, and therapeutic strategies. Our analysis reveals extensive interactions between these signaling pathways, with most being critically dependent on nuclear factor-kappa B (NF-κB). We propose that the nuclear factor-κB signaling pathway serves as a central hub in the mechanistic network of septic gut injury. By delineating the interplay of signaling pathways in intestinal damage during sepsis. This work aims to provide novel therapeutic perspectives.